(untitled) (Journal of NELTA, 2011)
Vocabulary is difficult to teach because of the complexity of its linguistic, semantic and psycho-cognitive aspects. So teachers should keep looking for ways to substitute rote repetition with more effective techniques. This paper first throws light on current research and practice in teaching vocabulary and moves on to explain some of the innovative methods for teaching vocabulary. The first strategy discussed is called "The Ripple Effect." According to this methodology the meanings of a word often radiates from the centre along several lines by focusing on different features of the original object. Another method in teaching vocabulary involves the use of colour as colours have tremendous influence on human beings. "The Word Wall" was originally designed to develop vocabulary learning skills and to internalize new vocabulary items. These three methods yield fruitful results in vocabulary acquisition. Key words: Ripple effect; Word wall approach; Using colour; Vocabulary Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 10-15 Uploaded date: 3 May, 2011 DOI: 10.3126/nelta.v15i1-2.4603